2018
DOI: 10.1530/erc-17-0435
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic thyroid carcinoma: review of treatment protocols

Abstract: Anaplastic thyroid carcinoma (ATC) is an orphan disease and in most patients fatal. So far no established treatment is available that prolongs survival. Several large retrospective studies have identified negative prognostic markers, analyzed efficacy of multimodal approaches such as radiotherapy with and without concurrent chemotherapy and chemotherapy protocols. Recently, single case reports have suggested some effectiveness of newer therapies targeting single somatic alterations in ATC. Overall, the conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 46 publications
(70 reference statements)
1
69
0
1
Order By: Relevance
“…22,23 Indeed, the median overall survival has not changed in the last decades. 24,25 It is well recognized that EMT represents a major mechanism of tumor progression and, in particular, in thyroid carcinogenesis. [26][27][28] Here, through an EMT profiler array, we found that JAM-A was one of the most downregulated genes in ATC and this was confirmed at the protein level.…”
Section: In Breast Cancers Both Overexpression and Downregulation Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Indeed, the median overall survival has not changed in the last decades. 24,25 It is well recognized that EMT represents a major mechanism of tumor progression and, in particular, in thyroid carcinogenesis. [26][27][28] Here, through an EMT profiler array, we found that JAM-A was one of the most downregulated genes in ATC and this was confirmed at the protein level.…”
Section: In Breast Cancers Both Overexpression and Downregulation Ofmentioning
confidence: 99%
“…Currently, there aren't any effective therapies for this disease . Indeed, the median overall survival has not changed in the last decades …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, analysis of different thyroid tumor entities revealed significant higher expression of CD1d and CD1d mRNA in ATCs compared to normal thyroid tissue and all other thyroid tumor types. On average, patients with ATCs survive only a few months after primary diagnosis . Although radiotherapy and different chemotherapies result in slightly improved survival rates, outcome is still very poor .…”
Section: Discussionmentioning
confidence: 99%
“…On average, patients with ATCs survive only a few months after primary diagnosis . Although radiotherapy and different chemotherapies result in slightly improved survival rates, outcome is still very poor . Therefore, several treatment strategies are currently under research .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation